Síntese e caracterização de AMBH utilizando 2,4,6-triacrilatoil-1,3,5-triazina como aceptor de Michael: novos híbridos moleculares com potencial atividade antineoplásica - Silva, Luciana Barbosa da (2018)
In this work, the synthesis and characterization of new trisubstituted 1,3,5-triazine derivatives with potential antineoplastic activity were performed. The strategy used consisted of molecular hybridization between the 1,3,5-triazine nucleus, pharmacophore group of numerous anticancer molecules, and nitroaromatic Morita-Baylis-Hillman adducts of proven biological activities, including anticancer activity. The first step consisted of the synthesis of 2,4,6-triacrylatoyl-1,3,5-triazine by means of an aromatic nucleophilic substitution between the cyanuric chloride and the potassium acrylate, using hydroquinone as an antipolymerizing agent. The second step consisted of a Morita-Baylis-Hillman reaction using nitroaromatic aldehydes, 2,4,6-triacrylatoyl-1,3,5-triazine (21) as Michael acceptor and DABCO as catalyst, resulting in the unpublished molecular hybrids (22a-c). The compounds showed satisfactory yields, between 60 and 80%. Several reaction conditions, solvents, conventional heating and microwave irradiation were investigated with the objective of optimizing yields. The structural characterization of these hybrids was performed using the Nuclear Magnetic Resonance (1H and 13C) and infrared techniques. To characterize 2,4,6-triacrylatoyl-1,3,5triazine (21), which is also an unpublished compound, the use of Gas Chromatography and Mass Spectrometry techniques was added.